PEMENUHAN HAK DAN KEWAJIBAN SUAMI ISTRI KELUARGA NELAYAN TAHUNAN - Mimbar, Munjait (Asian Journal of Law and Humanity, 2025)
This study aims to investigate the fulfillment of husband and wife rights and obligations in annual fishing families in Ketapang Village, Ulujami District, Pemalang Regency. The study used a qualitative method with a sociological approach, where humans serve as the primary research instrument, and data were obtained naturally through interactions with the research subjects. The sociological approach was used to understand the dynamics of social relations within fishing families, including the division of roles, responsibilities, and the adaptation processes that develop within them. The results show that the fulfillment of rights and obligations between husband and wife is based on mutual understanding and willingness of each party, although there are variations in practice in each fishing family. Husband and wife interactions are influenced by the fishermen's work patterns, which often require husbands to be away from home for long periods of time, so that the issue of fulfilling spiritual needs emerges as a major challenge. However, fishing couples are able to resolve these issues through patience, fortitude, and mutual understanding of each other's circumstances. Efforts to maintain marital harmony are carried out by building mutual trust, maintaining communication through video calls, and maintaining mutual commitment, so that family relations remain stable despite the limitations of time and space.